2013
DOI: 10.1007/s10499-013-9637-6
|View full text |Cite
|
Sign up to set email alerts
|

Increased carbon and nitrogen supplementation in Artemia culture ponds results in higher cyst yields

Abstract: This paper studied the effects of increased carbon (C) and nitrogen (N) supplementation in pond production of Artemia franciscana cysts in southern Vietnam. Pig manure and tapioca were used to supplement the natural food of Artemia in the ponds at a fixed C/N ratio 10. Addition of pig manure and tapioca at a standard rate (0.210 kg ww and 0.319 kg dw pond(-1) day(-1), respectively) was used as control. Increasing amounts of supplementation (110, 115, and 120 % of the control) were applied in three treatments. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 21 publications
0
20
0
Order By: Relevance
“…When stimulating biofloc formation in laboratory conditions by supplying C sources at different C/N rates, bacteria proved to be a relatively important food source for Artemia especially at lower algal feeding rations (Toi et al 2013), as demonstrated by 15 N stable isotope labelling and accumulation of specific biomarker fatty acids (Chamberlain et al 2005) in Artemia. Recent field work confirms that also in salt pond production conditions Artemia performance can be enhanced by carbon supplementation resulting in stimulation of bacterial biomass, although the process is much more difficult to steer due to the possible interference of environmental conditions, which may be difficult to control (Sui et al 2013;Ronald et al 2014).…”
Section: Artemiamentioning
confidence: 97%
See 1 more Smart Citation
“…When stimulating biofloc formation in laboratory conditions by supplying C sources at different C/N rates, bacteria proved to be a relatively important food source for Artemia especially at lower algal feeding rations (Toi et al 2013), as demonstrated by 15 N stable isotope labelling and accumulation of specific biomarker fatty acids (Chamberlain et al 2005) in Artemia. Recent field work confirms that also in salt pond production conditions Artemia performance can be enhanced by carbon supplementation resulting in stimulation of bacterial biomass, although the process is much more difficult to steer due to the possible interference of environmental conditions, which may be difficult to control (Sui et al 2013;Ronald et al 2014).…”
Section: Artemiamentioning
confidence: 97%
“…Recent field work confirms that also in salt pond production conditions Artemia performance can be enhanced by carbon supplementation resulting in stimulation of bacterial biomass, although the process is much more difficult to steer due to the possible interference of environmental conditions, which may be difficult to control (Sui et al . ; Ronald et al . ).…”
Section: Bacteria As Food In Aquaculturementioning
confidence: 99%
“…The annual demands for Artemia cysts has already increased on the world from a few tons in the mid 1970s to over 2,000 tons in the early 2000s (Sorgeloos, Dhert, & Candreva, 2001). Although the population consumption has been increasing rapidly, but the supply of Artemia cysts are not sufficient because the harvesting procedures are mainly performed gotten from natural salt lakes and solar salt-ponds (Sui, Wang, Nguyen, Sorgeloos, Bossier, & Stappen, 2013). Nevertheless, pond culture of Artemia has been developed and adopted by artisanal salt farmers over the past decades to produce the high quality cysts (Sui et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Although the population consumption has been increasing rapidly, but the supply of Artemia cysts are not sufficient because the harvesting procedures are mainly performed gotten from natural salt lakes and solar salt-ponds (Sui, Wang, Nguyen, Sorgeloos, Bossier, & Stappen, 2013). Nevertheless, pond culture of Artemia has been developed and adopted by artisanal salt farmers over the past decades to produce the high quality cysts (Sui et al, 2013). In Artemia production manuals, many efforts have made to help to choose suitable species/populations to be applied in aquaculture industry (Tackaert & Sorgeloos, 1991;Lavens & Sorgeloos, 1991Barata, Hontoria, & Amat, 1996;Thi, Van, & Sorgeloos, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Suitable salinity for Artemia growth and reproduction ranges from approximately 80–150 g L −1 (Van Stappen ). Food availability is important in hypersaline aquaculture systems, particularly in Artemia pond production where the density of Artemia is usually as high as 100–150 ind L −1 (Sui, Wang, Nguyen, Sorgeloos, Bossier & Van Stappen ). Current management in Artemia pond production mostly focuses on induction of a phytoplankton bloom by adding pig and chicken manure and inorganic fertilizers.…”
Section: Introductionmentioning
confidence: 99%